Biology Precedes, Culture Transcends: An Evolutionist's View of Human Nature - Ayala, Francisco J. (Zygon, 1998)
I will, first, outline what we currently know about the last 4 million years of human evolutionary history, from bipedal but small-brained Australopithecus to modern Homo sapiens, our species, through the prolific toolmaker Homo habilis and the continent wanderer Homo erectus. I shall then identify anatomical traits that distinguish us from other animals and point out our two kinds of heredity, the biological and the cultural. Biological inheritance is based on the transmission of genetic information, in humans very much the same as in other sexually reproducing organisms. But cultural inheritance is distinctively human, based on transmission of information by a teaching and learning process that is in principle independent of biological parentage. Cultural inheritance makes possible the cumulative transmission of experience from generation to generation. Cultural heredity is a swifter and more effective (because it can be designed) mode of adaptation to the environment than the biological mode. The advent of cultural heredity ushered in cultural evolution, which transcends biological evolution. I will, finally, explore ethical behavior as a model case of a distinctive human trait, and seek to ascertain the causal connections between human ethics and human biology. My conclusions are that (1) moral reasoning—that is, the proclivity to make ethical judgments by evaluating actions as either good or evil—is rooted in our biological nature; it is a necessary outcome of our exalted intelligence, but (2) the moral codes that guide our decisions as to which actions are good and which ones are evil are products of culture, including social and religious traditions. This second conclusion contradicts those evolutionists and sociobiologists who claim that the morally good is simply that which is promoted by the process of biological evolution.